2016
DOI: 10.1063/1.4948576
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of hexagonal Si-IV nanowires from extreme GPa pressure

Abstract: We use Raman spectroscopy in tandem with transmission electron microscopy and DFT simulations to show that extreme (GPa) pressure converts the phase of silicon nanowires from cubic (Si-I) to hexagonal (Si-IV) while preserving the nanowire's cylindrical morphology. In situ Raman scattering of the TO mode demonstrates the high-pressure Si-I to Si-II phase transition near 9 GPa. Raman signal of the TO phonon shows a decrease in intensity in the range 9 to 14 GPa. Then, at 17 GPa, it is no longer detectable, indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Therefore, the Si micro single-crystal light-emitting device is considered by the spectrum of EL rather than light emission by Joule heat like a filament. The main peak at 763 nm (1.625 eV) shows a characteristic similar to about 1.70 eV theoretically predicted as a quasidirect bandgap for the characteristic of the 2H-hexagonal Si structure [5,17,20,53,[61][62][63][64]. Figure 11(j) shows the Commission international de l'Eclairage (CIE) color coordinates for visible light emission of a Si single crystal.…”
Section: Performance Of Light Emission Of Si Crystalsupporting
confidence: 61%
“…Therefore, the Si micro single-crystal light-emitting device is considered by the spectrum of EL rather than light emission by Joule heat like a filament. The main peak at 763 nm (1.625 eV) shows a characteristic similar to about 1.70 eV theoretically predicted as a quasidirect bandgap for the characteristic of the 2H-hexagonal Si structure [5,17,20,53,[61][62][63][64]. Figure 11(j) shows the Commission international de l'Eclairage (CIE) color coordinates for visible light emission of a Si single crystal.…”
Section: Performance Of Light Emission Of Si Crystalsupporting
confidence: 61%
“…[6][7][8] Nevertheless, in group IV nanowires, the stability of novel polytypes -previously theoretically predicted 9 but experimentally observed only very locally in the form of crystal imperfections [10][11][12][13] is now supported by clear experimental evidences. [14][15][16][17][18][19] For instance, Vincent et al 14 reported the synthesis of quasi-periodic allotrope Ge heterostructures of hexagonal-diamond (wurtzite structure with single atom type) and cubic-diamond domains. These systems were obtained by a straininduced phase transformation in which size effects (in particular the preferential nucleation of dislocations on the wire surface and the activation of unusual slip planes) play a crucial role by lowering the value of the stress required by the cubic to hexagonal transition.…”
mentioning
confidence: 99%
“…Besson [ 31 ] reported for the first time that pure phases of Si( hP 4) and Si( hR 24) phases were prepared under hydrostatic pressure in the DAC method. When the pressure was increased to 12 GPa before returning to room pressure, the Si( cF 8)→Si( tI 4)→Si( cI 16) transitions took place in the microcrystalline phase, whereas Si( cI 16) changed into pure phase Si( hP 4) after annealing at 470 K for 2 h. In 2016, Smith [ 66 ] carried out the same study on silicon nanowires prepared by metal-assisted chemical etching (MACE). However, Raman measurements indicated that Si( hP 4) was the dominant phase in the recovered silicon nanowires without further annealing.…”
Section: Pathways To Exotic Metastable Silicon Allotropesmentioning
confidence: 99%